1999
DOI: 10.1897/1551-5028(1999)018<2275:qaogur>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

QUALITATIVE ASSESSMENT OF GENOTOXICITY USING RANDOM AMPLIFIED POLYMORPHIC DNA: COMPARISON OF GENOMIC TEMPLATE STABILITY WITH KEY FITNESS PARAMETERS IN DAPHNIA MAGNA EXPOSED TO BENZO[a]PYRENE

Abstract: A method of DNA profiling using the random amplified polymorphic DNA (RAPD) was used to assess toxicant-induced DNA effects in laboratory populations of Daphnia magna exposed to varying concentrations of the genotoxic hydrocarbon benzo[a]pyrene. These effects, represented by changes in the RAPD profiles, were compared with a number of key ecological fitness parameters (age-specific survival, age-specific fecundity, net reproductive rate, and intrinsic rate of population increase). Not only was the RAPD profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 0 publications
4
75
0
Order By: Relevance
“…In the present study, DNA damage was estimated using RAPD profiles that reflect DNA effects in treated plant seedlings. Previous studies have shown that changes in band patterns observed in DNA ‘fingerprint’ analyses reflect DNA alterations from single base changes (point mutations) to complex chromosomal rearrangements [18,45,46]. Similarly, in the present study, DNA damage induced by heavy metals was reflected by changes in RAPD profiles; disappearance of bands and appearance of new PCR products occurred in the profiles generated by exposed plants.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, DNA damage was estimated using RAPD profiles that reflect DNA effects in treated plant seedlings. Previous studies have shown that changes in band patterns observed in DNA ‘fingerprint’ analyses reflect DNA alterations from single base changes (point mutations) to complex chromosomal rearrangements [18,45,46]. Similarly, in the present study, DNA damage induced by heavy metals was reflected by changes in RAPD profiles; disappearance of bands and appearance of new PCR products occurred in the profiles generated by exposed plants.…”
Section: Discussionsupporting
confidence: 76%
“…''a'' is the number of band losses and appearance of new bands in DNA profiles and ''n'' is the number of bands detected in control DNA profiles. Calculated GTS values were compared with control GTS values (set to 100%) (Atienzar et al, 1999).…”
Section: Rapd-pcr Testmentioning
confidence: 99%
“…RAPD profiles generated from rats exposed to benzo [a] pyrene (B [a] P) revealed differences in the appearance and disappearance of bands in comparison to the RAPD profiles obtained from the control animals. RAPD methods have also been successfully used to detect DNA damage induced by radionuclides (Theodorakis and Shugart, 1997), mitomycin C (Becerril et al 1999), benzo [a] pyrene (Atienzar et al 1999;Atienzar et al 2002a, b;Castano and Becerril 2004), UV radiations, X-rays, gamma radiations (Kuroda et al 1999;Atienzar et al 2000;Jones and Kortenkamp 2000;Atak et al 2004;Hagger et al 2005), metals such as lead, manganese, cadmium and copper (Atienzar et al 2001;Liu et al 2005;Enan 2006), 17-ß estradiol (Atienzar et al 2002c).…”
mentioning
confidence: 99%